Hand Motion Analysis Illustrates Differences When Drilling Cadaveric and Printed Temporal Bone. (November 2022) - Hochman, Jordan B.; Pisa, Justyn; Kazmerik, Katrice; Unger, Bertram
Objective: Temporal bone simulation is now commonly used to augment cadaveric education. Assessment of these tools is ongoing, with haptic modeling illustrating dissimilar motion patterns compared to cadaveric opportunities. This has the potential to result in maladaptive skill development. It is hypothesized that trainee drill motion patterns during printed model dissection may likewise demonstrate dissimilar hand motion patterns. Methods: Resident surgeons dissected 3D-printed temporal bones generated from microCT data and cadaveric simulations. A magnetic position tracking system (TrakSTAR Ascension, Yarraville, Australia) captured drill position and orientation. Skill assessment included cortical mastoidectomy, thinning procedures (sigmoid sinus, dural plate, posterior canal wall) and facial recess development. Dissection was performed by 8 trainees (n = 5 < PGY3 > n = 3) using k-cos metrics to analyze drill strokes within position recordings. K-cos metrics define strokes by change in direction, providing metrics for stroke duration, curvature, and length. Results: T -tests between models showed no significant difference in drill stroke frequency (cadaveric = 1.36/s, printed = 1.50/s, P  < .40) but demonstrate significantly shorter duration (cadaveric = 0.37 s, printed = 0.16 s, P  < .01) and a higher percentage of curved strokes (cadaveric = 31, printed = 67, P  < .01) employed in printed bone dissection. Junior staff used a higher number of short strokes (junior = 0.54, senior = 0.38, P  < .01) and higher percentage of curved strokes (junior = 35%, senior = 21%, P  < .01). Conclusions: Significant differences in hand motions were present between simulations, however the significance is unclear. This may indicate that printed bone is not best positioned to be the principal training schema.